2014
DOI: 10.1371/journal.pone.0087448
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic Control of SPI1 Gene by CTCF and ISWI ATPase SMARCA5

Abstract: CCCTC-binding factor (CTCF) can both activate as well as inhibit transcription by forming chromatin loops between regulatory regions and promoters. In this regard, Ctcf binding on non-methylated DNA and its interaction with the Cohesin complex results in differential regulation of the H19/Igf2 locus. Similarly, a role for CTCF has been established in normal hematopoietic development; however its involvement in leukemia remains elusive. Here, we show that Ctcf binds to the imprinting control region of H19/Igf2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
(54 reference statements)
2
26
0
Order By: Relevance
“…The erythroid phenotype of Smarca5 deficiency is consistent with the previously reported SMARCA5 knockdown experiment that caused an inhibition of early erythroid differentiation and led to downregulation of β‐globin expression in human CD34+ progenitors and K562 cells . Interestingly, compared with erythropoiesis, the myelopoiesis in the Smarca5 mutant is affected less severely, consistent with SMARCA5 being a negative regulator of the myeloid transcriptional activator PU.1 . As downregulation of Gata1 does not directly induce apoptosis , we think that the cell death and cell cycle arrest of the Smarca5‐deficient erythroblasts is rather a result of the loss of Smarca5 function in cellular pathways other than Gata1 promoted differentiation.…”
Section: Discussionsupporting
confidence: 89%
“…The erythroid phenotype of Smarca5 deficiency is consistent with the previously reported SMARCA5 knockdown experiment that caused an inhibition of early erythroid differentiation and led to downregulation of β‐globin expression in human CD34+ progenitors and K562 cells . Interestingly, compared with erythropoiesis, the myelopoiesis in the Smarca5 mutant is affected less severely, consistent with SMARCA5 being a negative regulator of the myeloid transcriptional activator PU.1 . As downregulation of Gata1 does not directly induce apoptosis , we think that the cell death and cell cycle arrest of the Smarca5‐deficient erythroblasts is rather a result of the loss of Smarca5 function in cellular pathways other than Gata1 promoted differentiation.…”
Section: Discussionsupporting
confidence: 89%
“…We recently showed that SMARCA5 (together with the CTCF/cohesin complex) represses PU.1-mediated myeloid differentiation [7] and similarly, we noted that SMARCA5 regulates GATA1-mediated erythropoiesis [1]. We therefore next decided to analyze the levels of SPI1/PU.1 and GATA-1 transcripts with respect to SMARCA5.…”
Section: Cytogenetic Abnormalities and Gene Expression Dysregulation mentioning
confidence: 96%
“…Recently, a functional interplay of CTCF with the cohesin complex was reported to control PU.1 gene expression in myeloid cells 143 .…”
Section: Ctcf and Cohesin In Myeloid Biologymentioning
confidence: 99%
“…Moreover, CTCF knockdown led to derepression of PU.1 expression, suggesting that CTCF is a negative regulator of PU.1. Interestingly, the CTCF binding site within the PU.1 URE enhancer was cooccupied by the SWI/SNF complex member SMARCA5, leading to the idea that CTCF may cooperate with the SWI/SNF complex to act on nucleosomal remodeling at this locus 143 .…”
Section: Ctcf and Cohesin In Myeloid Biologymentioning
confidence: 99%